Prospective study of omental transposition in patients with chronic spinal injury. Issue 1 (1st July 2001) - Duffill, J; Buckley, J; Lang, D; Neil-Dwyer, G; McGinn, F; Wade, D
Abstract : OBJECTIVES: This prospective study was designed to assess the effects of omental transpostion in patients with a chronic spinal injury. METHODS: Neurological status was established to be stable and multiple baseline across patient studies were done preoperatively and repeated postoperatively. Assessments included activities of daily living (ADL), functional ability, degree of spasticity, motor power, sensation, pain perception, urodynamic studies, electromyography, sensory evoked potentials (SEPs), and infrared thermography to measure peripheral and general skin vascular responses. Each patient had MRI. Assessments were done at 3, 6, and 12 months after omental transposition in 17 patients. RESULTS: The detailed assessments failed to show significant improvement, although some patients showed minor objective and subjective change in some categories. Neurological deterioration occurred in one patient. There were 20 surgical complications including urinary tract infection, deep vein thrombosis, wound infection, and incisional hernia. CONCLUSIONS: Omental transposition has not been shown to improve neurological function in 17 patients with chronic spinal cord injury, and continued use of this operation in this situation is not supported by this study. Further advances in spinal cord repair may utilise the pedicled omental graft to provide an alternative vascular supply, but its current use should be limited to experimental models.